Petrographic, microstructural and petrophysical study of asphaltic limestone employed in the Late Baroque towns of the Val di Noto UNESCO site (south-eastern Sicily). (31st March 2023) - Punturo, R.; Indelicato, V.; Lanzafame, G.; Maniscalco, R.; Fazio, E.; Bloise, A.; Muschella, L.; Cirrincione, R.
Graphical abstract: Highlights: Pitchstone is used in the architecture of UNESCO World Heritage Site in SE Sicily. Multi-analytical study highlighted the intrinsic properties of this important valuable rock. Petrofabric-related properties affect the bitumen impregnation. Abstract: Pitchstone is one of the building materials used in the monumental architecture of the late Baroque towns of the Val di Noto (UNESCO World Heritage Site) in the Hyblean Plateau (SE Sicily). Our research goal is to define the relationships between microstructural properties and bitumen impregnation, which confer the distinctive shades and excellent physical–mechanical properties to this valuable geomaterial. The study has been conducted by optical microscopy, synchrotron X-ray microtomography, ultrasonic testing, gas chromatographic analysis, differential scanning calorimetry and thermogravimetry investigation on two differently impregnated samples, representative of the main exploited and marketed pitchstone lithotypes. It revealed a close relationship between petrofabric and petrophysical properties, and impregnation amount.